Exploring Christian Values in Educational Supervision: A Multi-Site Study on Implementing Value-Based Teaching Practices - Ferdinandus Lando; Burhanudin Burhanudin; Imron Arifin (Al-Qalam Institue, 2026)
This study aims to explore and analyze the implementation of Christian values, particularly those inspired by Galatians 5:22-23 (love, joy, peace, patience, kindness, goodness, faithfulness, gentleness, and self-control), in teaching supervision practices conducted by principals in Catholic elementary schools. A qualitative multi-site research design was employed, with data collected through classroom observations, in-depth interviews with principals and teachers, and document analysis related to supervisory practices. The findings indicate that principals consciously and unconsciously integrate these Christian values across all stages of supervision, including planning, classroom observation, and follow-up. Supervision is perceived not merely as performance evaluation but as a tool for holistic spiritual and professional development, fostering empathetic communication, constructive feedback, continuous support, and a harmonious and trustful work environment. Despite variations in supervisory style and emphasis across schools, the essence of value-based supervision remains consistent, enhancing teaching quality and strengthening teacher character in alignment with Catholic educational principles. The study contributes empirically and conceptually to understanding value-based leadership in education and offers practical guidance for developing spiritually grounded and relational supervisory practices.